Exocyst subunit EXO70J7 mediates cold-induced plasma membrane-associated vesicular trafficking and regulates cold tolerance in rice - Han Yun; Yongqi Ren; Shurong Wu; Gang Wei; Zhihang Guo; Ziyu Xie; Jiping Gao; Xiuzhi Du; Ruofei Cheng; Yunfeng Li; Guanghua He (Plant Science, 2026)

Solid-waste-derived reconstructed soil drives synergistic restoration of abandoned polymetallic mining sites: Evidence from soil properties and microbial network - Zhenran Mei; Zhongqiu Zhao; Ying He; Hang Bai; Mengchao Shi; Ruofei Li; Shun Jiang (Journal of Environmental Sciences, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Application-dependent effects of tea waste biochar on PFAS mobility and N2O and CH4 emissions in agricultural soil - Liting Hao; Dongdong Zhang; Ziheng Zhao; Jun Wang; Ruofei Wang; Miao Li (Waste Management, 2026)

Graph-Regularized Point-to-Trajectory Association for RS-AIS fusion toward maritime moving-ship identification and spatial refinement - Xin Du; Ruofei Zhong; Marco Scaioni; Marco Gianinetto; Shiyue Zhang; Qingyang Li; Zhenxing Sun; Chengming Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Orchestrating triacylglycerol biosynthesis and hydrolysis via synthetic genetic circuits enhances spinosad production in Streptomyces albus - Xiaochen Li; Ruofei Guo; Chanjuan Jiang; Ran Liu; Ji Luan; Hailong Wang (Bioresource Technology, 2026)

Mechanisms of extreme rainfall partitioning in contour ridge system: A modified SCS-CN method incorporating microtopographic and ridge geometry effects - Juan An; Guohui Li; Ruofei Liu; Yuanzhi Wu; Xiyuan Wu; Rui Zhang; Yao Zhao (Soil and Tillage Research, 2026)

Stepwise extraction of silicon and aluminum from nitric acid leach residue via sodium carbonate roasting and leaching - Fang Chen; Xue Ma; Lijun Jiang; Ruofei Du; Liangfeng Li; Laibao Liu; Xia Li; Bingyan Fan (Hydrometallurgy, 2026)

The deep colour consistency correction network for remote sensing images - Qingyang Li; Ruofei Zhong; Zhizhong Kang; Shihong Du; Wenqiang Lu; Xin Du; Yichun Chen (International Journal of Remote Sensing, 2026)

Low-barrier interface via noble metal induction for external energy-free ppb-level room-temperature formaldehyde sensing - Ziming Yang; Jiangnan Chang; Ying Qiao; Sitao Lv; Leqi Zhang; Yifei Fan; You Wu; Ruofei Lu; Hao Li; Yanan Guo; Patrick J. French; Jun Yin; et al. (Chemical Engineering Journal, 2026)

Integrated mangrove aquaculture systems enhance macrobenthic productivity: A case study in Zhanjiang, China - Haiping Huang; Yuanmin Sun; Kunxian Tang; Linjun Sun; Ruofei Zhang; Heyang Li; Yong Ma (Marine Pollution Bulletin, 2026)

Nano-biochar enhances energy taxis of Shewanella oneidensis MR-1 and the bio-utilization of minerals and Cr(VI) - Tianao Zhou; Min Li; Guangfei Liu; Huali Yu; Lecheng Liu; Ruofei Jin; Ziyi Zhang (Journal of Cleaner Production, 2026)

The research of a novelty bio-based flame retardant derived from the synthetic combination of alkaline-extracted polymer substances from wastewater sludge with phytic acid - Congcong Li; Ming Cheng; Ruiqin Chen; Ruofei Wang; Xiangyang Wang; Liang Zhao; Xiaodi Hao; Chen Shi; Wei Zhang (Journal of Environmental Management, 2026)

Construction of an efficient synergistic catalytic system using DBD plasma and Fe-TiO2-rGO/HCP catalytic coating for ofloxacin removal - Ming Li; Liang Guo; Yimo Zhao; Shanshan Huang; Ruofei Jia; Lijiao Zheng; Yongyang Chen; Shanping Li (Journal of Contaminant Hydrology, 2026)

Particle size–dependent molecular perturbations induced by copper nanoparticles in marine medaka (Oryzias melastigma): an integrated miRNA–mRNA analysis - Pengrui Ren; Peipei Zhang; Jingyuan Shi; Hongbo Li; Ruofei Jin; Hongjun Li (Frontiers in Marine Science, 2026)
Introduction Copper nanoparticles (Cu-NPs) have been increasingly released into marine environments due to their extensive applications, posing potential risks to marine organisms and human health. Although Cu-NPs of different particle sizes exhibit distinct toxicities—largely attributed to variations in specific surface area and Cu 2+ dissolution rates—current physicochemical parameters still fail to fully explain these toxic effects, and the underlying molecular mechanisms remain unclear. Methods This study aimed to investigate the toxic effects and underlying molecular mechanisms of Cu-NPs of different nominal primary diameters (10 nm, 50 nm, and 100 nm) on the marine medaka ( Oryzias melastigma ). Results LC 50 point estimates suggested slightly higher toxicity for smaller Cu-NPs. Integrated miRNAomic and transcriptomic analyses revealed that Cu-NPs-10 exposure markedly activated multiple metabolic pathways, including drug metabolism–cytochrome P450, retinol metabolism, and ascorbate and aldarate metabolism. Cu-NPs-50 exposure primarily affected neurodevelopment and synaptic signaling, with predicted miRNA–mRNA associations including miR-202 with mprip-like and miR-2187 with adgrg2-like . In contrast, Cu-NPs-100 exposure activated inflammation- and barrier repair-related networks, with potential miRNA–mRNA relationships involving miR-202 with tm4sf5 , miR-106a, miR-132c, miR-200b, and miR-202 with znfx1 , as well as miR-2187 and miR-202 with rhbdl2 . Discussion Collectively, the integrated miRNA–mRNA analysis suggests that smaller Cu-NPs show a correlation with more intense molecular stress responses than larger particles under seawater transformations (e.g., aggregation/dissolution), and provides insights into the key regulatory networks potentially underlying these size-associated responses.

Clinical management of autoimmune liver diseases: juncture, opportunities, and challenges ahead - Yangfan Chen; Ruofei Chen; Haiyan Li; Zongwen Shuai (Immunologic Research, 2025)

Localized strain induced carrier separation and filtering in S-scheme MgIn2S4@CdS heterojunction for boosting selective CO2 photoreduction - Xing'’an Dong; Weidong Dai; Chen Yang; Xiaoqian Li; Ruofei Tang; Xian Shi (Chemical Engineering Journal, 2025)

Research on the assembly and independent self-stress modes of one-dimension array tensegrity structures - Ruofei Li; Xingfei Yuan; Zhihong Zhang (Engineering Structures, 2025)

Scientometric insights into the human settlement environment in the karst regions: trends, challenges, and future directions - Xiaoqi Li; Ruofei Guan; Jiaojiao Zhu; Qichi Yang; Bin Zhang (Landscape and Ecological Engineering, 2025)

A 1DCNN-SENet-LSTM model for UGW-based automatic evaluation of grouting void location in post-tensioned concrete structure - Ruofei Liu; Longguan Zhang; Junfeng Jia; Shengli Li; He Guo; Binli Guo (Engineering Structures, 2025)

A candidate multi-epitopes vaccine against encephalomyocarditis virus confers protection in mice - Hongshan Li; Rongrong Cheng; Pingan Dong; Yongfang Chen; Rongqian Mo; Jiayu Yue; Dianyu Li; Yanmei Yang; Amjad Ali; Xiangrong Li; Ruofei Feng (Veterinary Microbiology, 2025)

Encephalomyocarditis virus non-structural protein 2C induces the degradation of NDP52 autophagy protein to promote its own survival - Rongqian Mo; Rongrong Cheng; Pingan Dong; Tingting Ma; Yaxin Zhang; Jingying Xie; Shasha Li; Huixia Li; Adi Idris; Xiangrong Li; Ruofei Feng (Veterinary Microbiology, 2025)

Extracellular vesicles engineered to directly target encephalomyocarditis virus ameliorates multi-organ viremia in a lethal infection model - Jiayu Yue; Yanmei Yang; Adi Idris; Wenjing Jin; Yaxin Zhang; Yongfang Chen; Xiangrong Li; Huixia Li; Shasha Li; Yanqiao Wen; Ruofei Feng; Jingying Xie (Veterinary Microbiology, 2025)

Enhanced catalytic ozonation of fiberboard wastewater using Ni-Cu co-doped Fe-ceramsite derived from sludge digestion residues - Qiang Zheng; Lei Li; Ruofei Jin; Qiuyan Ji; Xiumei Duan; Jiti Zhou; Tian Tian (Journal of Cleaner Production, 2025)

Impact performance of curved double arrow and stacked Miura-ori panels - Zhejian Li; Lingfeng Wang; Ruofei Yan; Yuanpeng He; Hong Hao; Yuanzheng Lin; Wensu Chen (Engineering Structures, 2025)

High dielectric sulfonyl-containing polyimide binders optimize the long-term stability and safety of NCM811 lithium-ion batteries at high voltages - Lin Chen; Dandan Yang; Junhao Xin; Xiaowei Zhou; Yuchen Zhang; Zixin Lv; Tiegen Guo; Qinghai Chen; Ruofei Gao; Ying Wang; Ning Wang; Shuanyan Kang; et al. (Chemical Engineering Journal, 2025)

Impact of steel slag, gypsum, and coal gangue on microbial immobilization of metal(loid)s in non-ferrous mine waste dumps - Ruofei Li; Jun Yao; Jianli Liu; Shun Jiang; Geoffrey Sunahara; Robert Duran; Miaomiao Li; Houquan Liu; Chuiyun Tang; Hao Li; Bo Ma; Bang Liu; et al. (Journal of Hazardous Materials, 2024)

Predictive modeling of patulin accumulation in apple lesions infected by Penicillium expansum using machine learning - Xiaoyan Cheng; Rongxia Li; Pengdong Xie; Xuexue Wang; Lirong Yu; Ruofei Wu; Huali Xue; Yang Bi (Postharvest Biology and Technology, 2024)

Body fluid multiomics in 3PM-guided ischemic stroke management: health risk assessment, targeted protection against health-to-disease transition, and cost-effective personalized approach are envisaged - Ruofei Chen; Xiaoyan Wang; Na Li; Olga Golubnitschaja; Xianquan Zhan (EPMA Journal, 2024)
Because of its rapid progression and frequently poor prognosis, stroke is the third major cause of death in Europe and the first one in China. Many independent studies demonstrated sufficient space for prevention interventions in the primary care of ischemic stroke defined as the most cost-effective protection of vulnerable subpopulations against health-to-disease transition. Although several studies identified molecular patterns specific for IS in body fluids, none of these approaches has yet been incorporated into IS treatment guidelines. The advantages and disadvantages of individual body fluids are thoroughly analyzed throughout the paper. For example, multiomics based on a minimally invasive approach utilizing blood and its components is recommended for real-time monitoring, due to the particularly high level of dynamics of the blood as a body system. On the other hand, tear fluid as a more stable system is recommended for a non-invasive and patient-friendly holistic approach appropriate for health risk assessment and innovative screening programs in cost-effective IS management. This article details aspects essential to promote the practical implementation of highlighted achievements in 3PM-guided IS management.

Eggshell powder as a bio-filler for starch and gelatin: Ternary biodegradable composite films manufactured by extrusion compression molding - Ting Li; Ruofei Li; Haodan Luo; Lu Peng; Jie Wang; Shasha Li; Man Zhou; Xiangyang Yuan; Zhiqing Zhang; Hejun Wu (Food Hydrocolloids, 2024)

Bioindicator responses to extreme conditions: Insights into pH and bioavailable metals under acidic metal environments - Ruofei Li; Jun Yao; Jianli Liu; Geoffrey Sunahara; Robert Duran; Beidou Xi; Zozo El-Saadani (Journal of Environmental Management, 2024)

Unraveling assemblage of microbial community dwelling in Dabaoshan As/Pb/Zn mine-impacted area: A typical mountain mining area of South China - Jian-li Liu; Jun Yao; Ruofei Li; Houquan Liu; Jun-jie Zhu; Geoffrey Sunahara; Robert Duran (Science of The Total Environment, 2024)

Alkaline-thermal hydrolysate of waste activated sludge as a co-metabolic substrate enhances biodegradation of refractory dye reactive black 5 - Xin Li; Tian Tian; Tiantian Cui; Baocun Liu; Ruofei Jin; Jiti Zhou (Waste Management, 2023)

Microbial metabolic activity in metal(loid)s contaminated sites impacted by different non-ferrous metal activities - Hao Li; Jun Yao; Ning Min; Geoffrey Sunahara; Jianli Liu; Miaomaio Li; Bang Liu; Wancheng Pang; Ying Cao; Ruofei Li; Robert Duran (Journal of Hazardous Materials, 2023)

Biomimetic optimized concept with Murray networks for accelerated solar-driven water evaporation - Ruofei Zhu; Ke Li; Dan Wang; Jipeng Fei; Jun Yan Tan; Shuzhou Li; Jichao Zhang; Hong Li; Shaohai Fu (Chemical Engineering Journal, 2023)

Ubiquitinomics revealed disease- and stage-specific patterns relevant for the 3PM approach in human sigmoid colon cancers - Hua Yang; Na Li; Liang Chen; Lei Zhou; Yuanchen Zhou; Jixiang Liu; Wenshuang Jia; Ruofei Chen; Junwen Su; Lamei Yang; Xiaoxia Gong; Xianquan Zhan (EPMA Journal, 2023)

AFLI-Calib: Robust LiDAR-IMU extrinsic self-calibration based on adaptive frame length LiDAR odometry - Weitong Wu; Jianping Li; Chi Chen; Bisheng Yang; Xianghong Zou; Yandi Yang; Yuhang Xu; Ruofei Zhong; Ruibo Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

5300‐Year‐old soil carbon is less primed than young soil organic matter - Jiao Su; Haiyang Zhang; Xingguo Han; Ruofei Lv; Li Liu; Yong Jiang; Hui Li; Yakov Kuzyakov; Cunzheng Wei (Global Change Biology, 2023)
Soils harbor more than three times as much carbon (C) as the atmosphere, a large fraction of which (stable organic matter) serves as the most important global C reservoir due to its long residence time. Litter and root inputs bring fresh organic matter (FOM) into the soil and accelerate the turnover of stable C pools, and this phenomenon is termed the “priming effect” (PE). Compared with knowledge about labile soil C pools, very little is known about the vulnerability of stable C to priming. Using two soils that substantially differed in age (500 and 5300 years before present) and in the degree of chemical recalcitrance and physical protection of soil organic matter (SOM), we showed that leaf litter amendment primed 264% more organic C from the young SOM than from the old soil with very stable C. Hierarchical partitioning analysis confirmed that SOM stability, reflected mainly by available C and aggregate protection of SOM, is the most important predictor of leaf litter‐induced PE. The addition of complex FOM (i.e., leaf litter) caused a higher bacterial oligotroph/copiotroph ( K ‐/ r ‐strategists) ratio, leading to a PE that was 583% and 126% greater than when simple FOM (i.e., glucose) was added to the young and old soils, respectively. This implies that the PE intensity depends on the chemical similarity between the primer (here FOM) and SOM. Nitrogen (N) mining existed when N and simple FOM were added (i.e., Glucose+N), and N addition raised the leaf litter‐induced PE in the old soil that had low N availability, which was well explained by the microbial stoichiometry. In conclusion, the PE induced by FOM inputs strongly decreases with increasing SOM stability. However, the contribution of stable SOM to CO 2 efflux cannot be disregarded due to its huge pool size.

Can urban rail transit reduce haze pollution? A spatial difference-in-differences approach - Yumei Lin; Meiling Li; Ruofei Lin (Environmental Science and Pollution Research, 2022)

Spatial and Seasonal Variations in the Stable Isotope Values and Trophic Positions of Dominant Zooplankton Groups in Jiaozhou Bay, China - Zhixin Ke; Ruofei Li; Danting Chen; Chunyu Zhao; Yehui Tan (Frontiers in Marine Science, 2022)
The spatial and seasonal distributions of stable carbon and nitrogen isotopes (δ 13 C and δ 15 N) in dominant zooplankton groups were investigated in Jiaozhou Bay. Zooplankton δ 13 C values ranged from −22.89‰ to −15.86‰, and δ 15 N values ranged from 3.18‰ to 13.57‰, respectively. The δ 13 C and δ 15 N values generally followed the order of small zooplankton < large calanoids < small Sagitta < large Sagitta . Spatial distribution patterns of zooplankton δ 13 C and δ 15 N values varied in different seasons. Our results suggested that the spatial variation of δ 13 C was mainly controlled by terrigenous organic matter (OM) input and phytoplankton biomass, but water temperature may have played a key role in the seasonal variation of δ 13 C. In spring, the high phytoplankton biomass might increase the δ 13 C value of small zooplankton in the inner bay. During other seasons, the δ 13 C values of zooplankton generally increased from the inner bay to the outer bay, which might be associated with the influence of 13 C-depleted terrigenous OM carried by the river discharge. Small zooplankton stable isotope values were significantly correlated with that of particulate organic matter (POM). The influence of anthropogenic nutrient input on isotopic baseline can be cascaded to the zooplankton, and the effect might be weak at higher trophic levels. The Bayesian standard ellipse areas of dominant zooplankton groups were generally smallest in the winter, suggesting a narrow niche width during that time. The niche partition between small zooplankton, large calanoids, and Sagitta was most distinct in winter, and followed by summer. The relative trophic level of Sagitta ranged from 2.23 to 4.01, which generally declined from the inner bay to the outer bay during the spring, autumn, and winter seasons. High anthropogenic nutrient loading might reduce the difference in trophic niches among zooplankton groups. This study provided detailed information on the distribution of zooplankton δ 13 C and δ 15 N in a coastal bay, which will be useful for understanding the anthropogenic influence on the ecosystem structure and function.

Does lower regional density result in less CO2 emission per capita? - Yumei Lin; Junpei Huang; Meiling Li; Ruofei Lin (Environmental Science and Pollution Research, 2022)

Acetone adsorption capacity of sulfur-doped microporous activated carbons prepared from polythiophene - Junchao Zhu; Ruofei Chen; Zheng Zeng; Changqing Su; Ke Zhou; Yamian Mo; Yang Guo; Fan Zhou; Jie Gao; Liqing Li (Environmental Science and Pollution Research, 2019)

Enhanced bioreduction of nitrobenzene by reduced graphene oxide materials: effects of surface modification and coexisting soluble electron shuttles - Guangfei Liu; Bin Dong; Jiti Zhou; Jing Wang; Ruofei Jin; Juanjuan Li (Environmental Science and Pollution Research, 2017)

National serosurvey of encephalomyocarditis virus in healthy people and pigs in China - Ruofei Feng; Jia Wei; Haixia Zhang; Jingjing Fan; Xiangrong Li; Dan Wang; Jingying Xie; Zilin Qiao; Mingsheng Li; Jialin Bai; Zhongren Ma (Archives of Virology, 2015)

A new hierarchical moving curve-fitting algorithm for filtering lidar data for automatic DTM generation - Wei Su; Zhongping Sun; Ruofei Zhong; Jianxi Huang; Menglin Li; Jingguo Zhu; Keshu Zhang; Honggan Wu; Dehai Zhu (International Journal of Remote Sensing, 2015)

Site-directed mutagenesis of substrate binding sites of azoreductase from Rhodobacter sphaeroides - Guangfei Liu; Jiti Zhou; Jing Wang; Bin Yan; Jingmei Li; Hong Lu; Yuanyuan Qu; Ruofei Jin (Biotechnology Letters, 2008)

Good response in a patient with deep-seated subcutaneous ulcer due to Candida species - Liyan Xi; Xiqing Li; Junmin Zhang; Changming Lu; Ting Xie; Ruofei Yin (Mycopathologia, 2007)